2019
DOI: 10.1021/acs.est.9b00272
|View full text |Cite
|
Sign up to set email alerts
|

Clothing-Mediated Exposures to Chemicals and Particles

Abstract: A growing body of evidence identifies clothing as an important mediator of human exposure to chemicals and particles, which may have public health significance. This paper reviews and critically assesses the state of knowledge regarding how clothing, during wear, influences exposure to molecular chemicals, abiotic particles, and biotic particles, including microbes and allergens. The underlying processes that govern the acquisition, retention and transmission of clothing-associated contaminants and the consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 243 publications
(503 reference statements)
3
87
0
1
Order By: Relevance
“…The persistently higher concentration of benzothiazole in the room relative to the supply air indicates a building source. Benzothiazole has been reported as an emission in classrooms, 9 homes, 14 in small quantities in breath, 50,51 skin, 51,52 and new clothing 53 . Although there may be a small contribution from breath and skin as athletes enter the room, the majority of benzothiazole emission is attributed to outgassing from the room flooring, which is made from crumb rubber.…”
Section: Resultsmentioning
confidence: 99%
“…The persistently higher concentration of benzothiazole in the room relative to the supply air indicates a building source. Benzothiazole has been reported as an emission in classrooms, 9 homes, 14 in small quantities in breath, 50,51 skin, 51,52 and new clothing 53 . Although there may be a small contribution from breath and skin as athletes enter the room, the majority of benzothiazole emission is attributed to outgassing from the room flooring, which is made from crumb rubber.…”
Section: Resultsmentioning
confidence: 99%
“…96 Other recent studies have shown how soiled clothing protects us from gas-phase oxidants but can also enhance dermal exposure to chemical pollutants. 141,205,250,251 Residence time, light and oxidant levels. Also different from outdoors is the short, roughly hour-long residence time of indoor air, and the lower concentrations of gas-phase oxidants and light.…”
Section: Discussionmentioning
confidence: 99%
“…Given the presence of amines in outdoor air that ventilates buildings, amines are also common constituents of indoor air, including airborne particles, and in indoor surface films. Indoor sources of amines, in addition to outdoor‐to‐indoor transport, include smoking 404‐408 ; cooking 274,313,409,410 ; anticorrosive agents used in humidification or HVAC units 411‐413 ; textiles and textile carpet tiles 414,415 ; and the decomposition of casein‐containing building materials 416 . Amines, amino acids, and urea are also known constituents of human skin 417‐422 .…”
Section: Acids and Basesmentioning
confidence: 99%
“…Aniline-based dyes are commonly used in textiles. 415 The extent to which such dyes migrate from clothing to indoor environments is not known. Sollinger et al 414…”
Section: Textiles and Textile Carpetsmentioning
confidence: 99%